Complex-phase bainite steel containing multi-scale and multi-form retained austenite structure and preparation method of complex-phase bainite steel

By adopting the chemical composition of low-carbon aluminum-containing silicon steel in bainite steel and two-step isothermal quenching treatment in bainite steel, the problems of low production efficiency and insufficient performance in the preparation process of existing bainite steel are solved, and high strength, high hardness, good plasticity and toughness are achieved.

CN119876787APending Publication Date: 2025-04-25HEBEI UNIV OF ENG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510119941.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing bainite steel requires long-term isothermal quenching during the preparation process, resulting in low production efficiency, and high carbon content affects welding performance and plastic/toughness properties. The high silicon content weakens the steel surface quality and electroplating coating ability.

Method used

The chemical composition of low-carbon aluminum-containing silicon steel is adopted, and through two-step isothermal quenching heat treatment, isothermal quenching is performed below and above the starting temperature point of the martensite transformation to shorten the completion time of bainite transformation, refine the bainite slat structure, and form a multi-scale and multi-morphological residual austenite distribution.

Benefits of technology

The high strength, high hardness, good plasticity and toughness properties of bainite steel are achieved, which shortens production time, reduces production costs, and improves welding performance and surface quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876787A_ABST
    Figure CN119876787A_ABST
Patent Text Reader

Abstract

The invention discloses complex-phase bainite steel containing a multi-scale and multi-form retained austenite structure. The complex-phase bainite steel comprises the following chemical components in percentage by mass: 0.28 to 0.45 percent of C, 0.6 to 1.35 percent of Al, 0.65 to 1.1 percent of Si, 1.6 to 2.0 percent of Mn, 1.5 to 1.8 percent of Cr, 0.28 to 0.5 percent of Ni, 0.28 to 0.5 percent of Mo, 0.15 to 0.28 percent of W and Plt, 0.008, S < lt >; 0.008, the balance being Fe; the complex-phase bainite steel is prepared by austenitizing a steel billet and then carrying out two-step staged isothermal quenching heat treatment, the temperature of one-step isothermal quenching heat treatment is set to be lower than the martensite transformation starting temperature point of the steel billet, and the temperature of the other-step isothermal quenching heat treatment is set to be higher than the martensite transformation starting temperature point of the steel billet. The complex-phase bainite steel disclosed by the invention has a multi-scale and multi-form retained austenite structure with a proper content, so that the complex-phase bainite steel has the advantages of high strength, high hardness, good plasticity, good toughness and the like in the aspect of comprehensive mechanical properties, and the complex-phase bainite steel is simple in preparation process, short in flow and easy for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bainite steel materials, in particular to a complex-phase bainite steel containing a multi-scale and multi-morphological residual austenite structure, and preparation of the complex-phase bainite steel. Background Art

[0002] Since its discovery, bainite structure has been widely concerned and continuously studied by materials workers at home and abroad because of its excellent comprehensive performance and its help in reducing production costs. In particular, in recent years, based on the research results of bainite phase transformation theory and the role of alloying elements in steel, a series of bainite steels with high strength and hardness have been developed using high-carbon and high-silicon steels. The excellent mechanical properties of this bainite steel are mainly attributed to the micro-nanoscale bainite laths in its microstructure and the film-like residual austenite structure parallel to these laths. However, in order to obtain these smaller-scale bainite structures, it is often necessary to perform isothermal quenching treatment at a lower temperature for dozens or even hundreds of hours, resulting in low industrial production efficiency and limited production scale. In addition, the high carbon content will also have an adverse effect on its welding performance and plastic / toughness properties, and the high silicon content will weaken the surface quality and electroplating coating ability of the steel, thereby restricting the application of this type of high-strength steel as a structural material in industrial production.

[0003] Studies have reported that adding cobalt (Co) and aluminum (Al) alloying elements to high carbon steel can increase the free energy difference between bainite and austenite, thereby accelerating the bainite transformation. This method has shortened the bainite transformation time to a certain extent, but the isothermal transformation time of high carbon bainitic steel is still as long as dozens of hours, and the addition of the relatively expensive Co element is not conducive to reducing production costs.

[0004] There are also studies that prepare Fe-Mn-Ni-C low-carbon bainitic steel by replacing part of the carbon (C) element with nickel (Ni). Its microstructure is composed of bainite laths and residual austenite. The low carbon content improves the welding performance of the steel to a certain extent. The residual austenite with a high content and distribution characteristics in different scale ranges can promote the simultaneous increase of steel plasticity and toughness due to the transformation induced plasticity (TRIP) effect caused by deformation. However, the bainite laths that tend to merge and coarsen reduce the strength and hardness of the steel. At the same time, the relatively expensive price of the Ni element is not conducive to controlling production costs.

[0005] In addition, there are studies that reduce the carbon content in high-carbon high-silicon steel, replace part of the silicon (Si) element with Al, and then undergo a isothermal quenching treatment at a higher temperature and a shorter holding time to obtain a bainitic steel composed of bainite laths and retained austenite. The fine structure of bainite laths in this type of steel is an important condition for its high strength, and the TRIP effect of the blocky retained austenite of different sizes provides the possibility for it to have good plasticity / toughness. However, the control of alloying elements and heat treatment processes involved in the composition design and preparation of bainitic steel is difficult to solve. For example, although the increase in the addition of Al elements helps to refine the bainite laths, it will reduce the fluidity of the molten liquid during the steel pouring process, which is not conducive to casting; the temperature and holding time of diffusion annealing, austenitization and isothermal quenching will affect the content of retained austenite in the microstructure, the size distribution range and the size of the bainite laths, and then affect the comprehensive mechanical properties of bainitic steel.

[0006] Therefore, research on bainitic steel is still ongoing. If a steel grade that has both mechanical and processing performance advantages and is easy to produce can be developed, it will have broad significance and value for the application and development of bainitic steel. Summary of the invention

[0007] In order to make up for the shortcomings of existing bainitic steels, the present invention provides a complex-phase bainitic steel with a simple preparation process, a short process, and easy industrial production. Its microstructure consists of an appropriate amount of residual austenite structure and a fine-sized bainite lath structure with multi-scale and multi-morphological distribution, and exhibits the advantages of high strength, high hardness, good plasticity and toughness in terms of comprehensive mechanical properties.

[0008] To achieve the above-mentioned object, the present invention provides a multi-phase bainite steel containing a multi-scale and multi-morphological retained austenite structure, comprising the following chemical components in mass percentage: C 0.28-0.45, Al 0.6-1.35, Si 0.65-1.1, Mn 1.6-2.0, Cr 1.5-1.8, Ni 0.28-0.5, Mo 0.28-0.5, W 0.15-0.28, P <0.008, S <0.008, and the rest is Fe;

[0009] The complex phase bainite steel is prepared by subjecting a steel billet to austenitization and then subjecting it to two-step isothermal quenching heat treatment, wherein the temperature of one step of the isothermal quenching heat treatment is below the martensitic transformation start temperature of the steel billet, and the temperature of the other step of the isothermal quenching heat treatment is above the martensitic transformation start temperature of the steel billet.

[0010] As a limitation of the above technical solution, the martensitic transformation starting temperature point, denoted as Ms point, is calculated from the isothermal transformation curve of the bainitic transformation zone, namely the TTT curve (Time Temperature Transformation Curve), and the bainitic transformation starting temperature point is calculated at the same time, denoted as Bs point; the Ms point, Bs point and the critical temperature A of the austenite transformation of the steel billet are then measured using a quenching dilatometer. c3 Confirm the curve.

[0011] The complex phase bainite steel of the present invention is a low carbon aluminum-silicon steel with a low C element content. Compared with high carbon bainite steel, it exhibits good weldability and cold working formability. Moreover, due to the higher Ms point of low carbon steel, the bainite transformation completion time is shortened to a certain extent.

[0012] In order to ensure that low-carbon steel still has high strength, the T0 curve is improved by adding Al alloy elements to increase the nucleation driving force and nucleation density during bainite transformation, so as to achieve the purpose of refining bainite laths and improving the strength of bainite steel. Moreover, these bainite laths divide the blocky austenite into different structural units, making it present a multi-scale and multi-morphological distribution feature. The addition of Al elements can also inhibit the precipitation of brittle carbides during bainite transformation because Al has a similar effect to Si elements, improve the shortcomings of poor surface quality and surface coating performance caused by excessive Si elements, and at the same time, the increase of its plasticity / toughness due to the absence of brittle carbides is also promoted; further shortening the completion time of bainite transformation, improving production efficiency, reducing energy, time and cost investment in production, and facilitating industrial production and application.

[0013] In addition, the addition of Mn, Cr and Mo elements can improve the hardenability of steel and ensure the process stability and organizational uniformity of larger-sized products in production, while also reducing the transformation temperature of bainite and also playing the role of refining bainite laths.

[0014] While adjusting the chemical composition as above, a two-step isothermal quenching heat treatment is performed below the Ms point of the steel billet and above the Ms point (below / above the Ms point), so that the formed lamellar bainite structure has a small size, and these lamellars contain a high dislocation density, which plays an important role in promoting the simultaneous increase of the strength and toughness of bainitic steel. The fine lamellar martensite formed by isothermal quenching below the Ms point is equivalent to undergoing a medium-temperature tempering treatment after subsequent isothermal quenching above the Ms point. This process greatly reduces the brittleness of the martensite, so that it strengthens the steel and promotes the increase in toughness. Or the austenite retained after isothermal quenching above the Ms point forms martensite during the isothermal quenching process below the Ms point. Although it has not been tempered, it does not show high brittleness due to the small degree of supercooling it has experienced, which will not have an adverse effect on the increase in toughness, but will instead play a beneficial role in promoting the improvement of strength. Ultimately, a microstructure consisting of ultrafine-structured bainite laths, multi-scale and multi-morphological retained austenite, and a small amount of martensite can be formed.

[0015] A large number of studies have pointed out that the retained austenite in the microstructure is prone to undergo martensitic transformation during deformation, resulting in transformation induced plasticity (TRIP) effect and transformation martensitic strengthening, thereby increasing the strength and plasticity / toughness of the steel at the same time. The TRIP effect mainly depends on the stability of the retained austenite and the degree (or percentage) of martensitic transformation during deformation. It is reported that the larger the size of the retained austenite, the worse its stability is, and martensitic transformation can occur under small stress / strain (caused by external load). However, as the size of the retained austenite decreases, its stability shows a trend of gradual increase, and the stress / strain required for martensitic transformation also increases. Therefore, as the tensile or bending load increases, the retained austenite with multi-scale distribution characteristics will undergo martensitic phase transformation in sequence from large to small according to its scale distribution range, followed by a continuous TRIP effect and a continuous high strain hardening behavior, thereby achieving the goal of simultaneously improving the strength and plasticity / toughness of the steel. This is precisely the advantage of the multi-scale and multi-morphological retained austenite in the microstructure of the steel of the present invention, that is, this microstructure enables the steel of the present invention to maintain high strength and hardness while also showing good plasticity and toughness, solving the problem that strength, hardness, plasticity and toughness are contradictory and difficult to coexist, thereby having significantly excellent comprehensive mechanical properties.

[0016] As a limitation of the above technical solution, the temperature of the isothermal quenching heat treatment below the Ms point is Ms-90°C to Ms°C, and the temperature of the isothermal quenching heat treatment above the Ms point is Ms°C to Ms+100°C.

[0017] As a limitation of the above technical solution, the temperature fluctuation of the two-step isothermal quenching heat treatment process is controlled within ±3°C.

[0018] As a limitation of the above technical solution, the time of the two-step staged isothermal quenching heat treatment is as follows:

[0019] The first step is to perform isothermal quenching below the Ms point for 0.5min to 65min, and the second step is to perform isothermal quenching above the Ms point for 30min to 120min;

[0020] Or the first step is to perform isothermal quenching above Ms for 0.5min to 35min, and the second step is to perform isothermal quenching below Ms point for 30min to 130min.

[0021] According to the TTT curve, Ms point, Bs point and A c3 Curves, etc. determine the detailed process parameters of the staged isothermal quenching heat treatment below / above the Ms point of the steel of the present invention to obtain a complex-phase bainite steel with excellent comprehensive properties.

[0022] The present invention also provides a method for preparing the complex-phase bainite steel containing a multi-scale and multi-morphological retained austenite structure as described above, comprising the following preparation steps:

[0023] a. Melting and casting into steel ingots according to the chemical composition, and then forging to obtain steel billets;

[0024] b. Preparation of complex phase bainite steel:

[0025] b-1. Use JMatPro software to calculate the isothermal transformation curve (TTT curve) of the steel billet in the bainite transformation zone, determine the Ms point, and after confirming the Ms point using a quenching dilatometer, determine the process parameters suitable for the two-step isothermal quenching heat treatment of the steel billet;

[0026] b-2. Homogenization treatment of steel billet;

[0027] b-3. The steel billet after homogenization treatment is austenitized;

[0028] b-4. Two-step isothermal quenching treatment: immediately quench the austenitized sample into a molten salt bath at Ms-50℃~Ms-10℃ and keep it warm for 3min~30min, then immediately quench the sample into a molten salt bath at Ms+10℃~Ms+60℃ and keep it warm for 30min~100min. After the warming time is over, take out the sample immediately and cool it to the ambient temperature in the air;

[0029] Or immediately quench the sample after austenitization into a molten salt bath at Ms+20℃~Ms+60℃ and keep it warm for 5min~35min, then immediately quench the sample into a molten salt bath at Ms-50℃~Ms-10℃ and keep it warm for 30min~125min. After the holding time is over, take out the sample immediately and cool it to the ambient temperature in the air.

[0030] The two-step isothermal quenching process can be isothermal quenching below the Ms point first and then isothermal quenching above the Ms point, or isothermal quenching above the Ms point first and then isothermal quenching below the Ms point.

[0031] If isothermal quenching below the Ms point is first used, a fine lamellar martensite structure can be obtained. These martensite structures, on the one hand, consume a certain amount of supercooled austenite structure, and on the other hand, provide a large number of nucleation points for the subsequent isothermal quenching below the Ms point and the further transformation of bainite in the next stage of isothermal quenching above the Ms point, which not only shortens the completion time of bainite transformation, but also refines the bainite laths; at the same time, the fine structure martensite and bainite structures formed successively divide the residual austenite into structural units of different scales and morphologies, so that the residual austenite forms large blocks, medium blocks, small blocks and film-like structures, so that the residual austenite presents a wider scale distribution range.

[0032] If isothermal quenching is first performed at a relatively high temperature above the Ms point, some residual austenite structures with larger scale and higher content can be obtained. These residual austenites become carbon-rich due to the absorption of carbon elements discharged from the inside of the bainite, making it easier to retain them at room temperature. In addition, since the isothermal quenching time above the Ms point is shorter than the theoretical bainite transformation completion time of the steel of the present invention, the bainite transformation is not complete, so that part of the untransformed supercooled austenite will continue to undergo bainite transformation during the isothermal quenching process below the Ms point, accompanied by the formation of martensite. These bainite and martensite are not only small in size, but can also be divided into large blocks, medium blocks, small blocks and film-like structures by consuming the residual austenite, which also widens the size distribution range of the residual austenite.

[0033] As a limitation of the above technical solution, step a, using a vacuum high-frequency induction furnace for melting, pouring the molten steel into a mold, slowly cooling it to the ambient temperature to obtain a steel ingot in a cast state; removing the oxide layer on the outer surface of the steel ingot, cutting off the bottom part containing inclusions, and removing the riser, and then heating it to about 1200°C, keeping it warm for 8 to 10 hours, and then taking it out of the furnace for forging, maintaining the final forging temperature >860°C, forging it into a steel billet, and air cooling it to room temperature.

[0034] As a limitation of the above technical solution, the homogenization treatment of the steel billet in step b-2 is as follows:

[0035] The forged steel billet is heated to 1130-1180°C in a vacuum resistance furnace, kept warm for 10-12 hours, and then slowly cooled for diffusion annealing to eliminate composition and organizational heterogeneity.

[0036] The annealing temperature and holding time can avoid the coarsening and overburning of the original austenite grains, eliminate the uneven structure and component segregation of the cast ingot, ensure the uniformity of the ingot structure and composition, and provide conditions for obtaining uniformly distributed bainite and residual austenite structures in subsequent isothermal quenching treatment.

[0037] As a limitation of the above technical solution, step b-3 is to heat the steel billet after homogenization treatment to 920-980°C and keep it warm for 20-35 minutes to perform austenitization treatment by putting it into the furnace at a temperature reached.

[0038] As a limitation of the above technical solution, the salt bath used in step b-4 is a mixed salt bath of sodium nitrite and potassium nitrate, wherein the mass ratio of sodium nitrite to potassium nitrate is generally 1:1.

[0039] The operations of smelting, forging, homogenizing and austenitizing of the steel billet during the preparation of the complex-phase bainitic steel of the present invention are further improved, wherein the homogenizing annealing temperature, the austenitizing temperature and the temperature of the isothermal quenching below / above the Ms point are all determined by the chemical composition of the steel of the present invention, so as to prepare bainitic steel with excellent performance.

[0040] In summary, the bainite steel of the present invention is a low-carbon aluminum-containing silicon steel. Through the combination and optimization of chemical composition and staged austempering treatment process, the bainite laths are refined and the strength of the bainite steel is improved. These bainite laths divide the blocky austenite into different structural units, so that it presents multi-scale and multi-morphological distribution characteristics. Compared with traditional medium-carbon and low-carbon bainite steels, the residual austenite in its microstructure is not only multi-scale, multi-morphological and with a wide scale distribution range, but also specifically manifested in that most of the residual austenite structure is concentrated between 0.4 and 4 μm, followed by between 4 and 6 μm, and a small part of the scale is greater than 6 μm; and the average thickness of the bainite laths is about 130 nm, which is significantly refined. This microstructure enables the steel of the present invention to exhibit good plasticity and toughness while maintaining high strength and hardness, and the specific mechanical performance parameters reach: tensile strength 1429MPa, yield strength 1112MPa, elongation 19%, impact absorption energy 112J, hardness 431HV, showing significantly excellent comprehensive mechanical properties. In addition, the preparation of the complex phase bainite steel of the present invention has simple process, short process, easy operation, strong practicality, and can be mass-produced industrially, which is conducive to promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1, XRD spectrum of the complex phase bainite steel of Example 1.

[0042] Figure 2 , Optical microscope photograph of the microstructure of the complex phase bainite steel of Example 1.

[0043] Figure 3 , Transmission electron microscope photograph of the microstructure of the complex phase bainite steel of Example 1.

[0044] Figure 4 , Engineering stress-strain curve of complex phase bainitic steel in Example 1.

[0045] Figure 5 , Transmission electron microscope photograph of the microstructure of the comparative complex bainite steel.

[0046] Figure 6 , engineering stress-strain curve of comparative complex phase bainitic steel. DETAILED DESCRIPTION

[0047] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] The raw materials used in the following examples and comparative examples are typical products purchased from the market. The quantitative tests are repeated three times and the results are averaged.

[0049] Example 1

[0050] A complex phase bainite steel and its preparation.

[0051] The chemical composition by mass percentage (wt.%) is: C 0.29%, Al 1.17%, Si 0.70%, Mn 1.66%, Cr 1.65%, Ni 0.31%, Mo 0.38%, W 0.16%, S 0.0044%, P 0.0032%, and the rest is Fe.

[0052] Prepare as follows:

[0053] a. The above raw materials are melted in a vacuum high-frequency induction furnace, and the molten steel is poured into a 50kg mold with a riser, and then slowly cooled to the ambient temperature (or room temperature) to obtain a steel ingot in a casting state, which is called an ingot; the ingot is turned to remove the outer surface oxide layer, the part containing inclusions at the bottom of the ingot is cut off, and the riser is removed, and then heated to about 1200°C, kept warm for 8 to 10 hours, and then taken out of the furnace for forging treatment, during which the final forging temperature is maintained at>860°C, and forged into a rod-shaped billet with a cross-sectional area of ​​40mm×60mm and a length of 800mm, air-cooled to room temperature, and finally cut with a cutting machine to obtain a smaller sample as a steel billet for subsequent processing, and coated with a high-temperature resistant and anti-oxidation coating.

[0054] b. Preparation of Dual-phase Bainite Steel

[0055] b-1. Based on the chemical composition of the steel, the bainite transformation starting temperature (Bs point) of the steel was calculated by JMatPro software and determined by quenching dilatometer to be 499°C, the martensite transformation starting temperature (Ms point) was 309°C, and the TTT curve determined that the bainite transformation completion time at 350°C was approximately 40 minutes.

[0056] b-2. Heat the forged steel billet coated with high-temperature anti-oxidation coating to 1130-1170°C in a vacuum resistance furnace, keep it warm for 10-12 hours, and then slowly cool it for diffusion annealing, i.e., homogenization treatment, to eliminate composition and organizational heterogeneity.

[0057] b-3. The homogenized steel billet is heated to 930°C and kept at this temperature for 30 minutes for austenitizing treatment.

[0058] b-4. Perform a two-step isothermal quenching treatment: immediately take out the austenitized sample and quench it into a molten salt bath (a mixed salt of sodium nitrite and potassium nitrate at a mass ratio of 1:1, the salt bath used in the following embodiments is the same) at 280°C (below Ms point, Ms-29°C) for 5 minutes, and then quench it again into a molten salt bath at 350°C (above Ms point, Ms+41°C) for 60 minutes to complete the bainite transformation. During this period, the temperature fluctuation is controlled within ±3°C. After the insulation time is over, take it out immediately and cool it to ambient temperature in the air.

[0059] The temperature and time of austempering below the Ms point can ensure that part of the retained austenite is transformed into fine-scale martensite and bainite structures, which can divide the retained austenite into different units on the one hand, and provide a large number of nucleation points for the subsequent bainite transformation by austempering above the Ms point on the other hand, making it possible to refine the bainite laths. The subsequent austempering temperature and time above the Ms point can ensure that the bainite completes the transformation and avoids the generation of high-temperature temper brittleness. In this process, the transformation of bainite further divides the retained austenite into structural units of different scales, providing a strong guarantee for obtaining multi-scale, multi-morphological and appropriate content retained austenite, as well as the formation of fine bainite laths.

[0060] A complex phase bainite steel consisting of bainite (BCC structure) and retained austenite (FCC structure) was prepared. Figure 1 As shown in the XRD spectrum, it has the characteristics of multi-scale and multi-morphological distribution of appropriate content of retained austenite, as well as fine bainite lath structure, as shown in the attached Figure 2 The microstructure optical microscope picture of the microstructure is shown in Figure 2. According to statistics of a large number of microstructure optical microscope pictures, the size of the blocky retained austenite is mostly concentrated in the range of 0.4 to 4 μm, followed by 4 to 6 μm, and a small part of the size is > 6 μm; the average volume fraction of retained austenite is 8.5%; and the average thickness of bainite lath is about 130 nm, see the attached Figure 3 Microstructure transmission electron microscope picture. According to the uniaxial tensile test, the tensile strength of the steel of the present invention is 1429MPa, the yield strength is 1112MPa, and the elongation is 19%. Figure 4 Engineering stress-strain curve; through Charpy impact test, the impact absorption energy of the steel of the present invention is 112J, the hardness is 431HV, and the comprehensive mechanical properties are excellent.

[0061] Example 2

[0062] The difference between this embodiment and Example 1 is that the process parameters of the two-step isothermal quenching treatment in the preparation process are different, and the obtained complex phase bainite steel has differences in microstructure and mechanical properties. The specific preparation is as follows:

[0063] The chemical composition and preparation steps a to b-3 are the same as those in Example 1;

[0064] b-4. Perform a two-step isothermal quenching treatment: immediately take out the austenitized sample and quench it into a molten salt bath at 280°C (below Ms point, Ms-29°C) for 10 minutes, then quench it again into a molten salt bath at 350°C (above Ms point, Ms+41°C) for 90 minutes, during which the temperature fluctuation is controlled within ±3°C. After the insulation time is over, take it out immediately and cool it to room temperature in the air.

[0065] The prepared complex phase bainite steel has the characteristics of multi-scale and multi-morphological distribution of appropriate content of retained austenite, as well as fine bainite lath structure; the size distribution of blocky retained austenite is mostly concentrated in the range of 0.4-3μm, followed by 3-5μm, and a small part of the size is >5μm, the average volume fraction of retained austenite is 7.9%, and the average thickness of bainite lath is about 140nm. According to the uniaxial tensile test, the tensile strength of the steel is 1416MPa, the yield strength is 1107MPa, and the elongation is 17.2%; according to the Charpy impact test, the impact absorption energy of the steel of the present invention is 93J, and the hardness is 442HV, showing excellent comprehensive mechanical properties.

[0066] Example 3

[0067] The difference between this embodiment and Example 1 is that the process parameters of the two-step isothermal quenching treatment in the preparation process are different, and the obtained complex phase bainite steel has differences in microstructure and mechanical properties. The specific preparation is as follows:

[0068] The chemical composition and preparation steps a to b-3 are the same as those in Example 1;

[0069] b-4. Perform a two-step isothermal quenching treatment: immediately take out the austenitized sample and quench it into a molten salt bath at 350°C (above Ms point, Ms+41°C) for 30 minutes, then immediately quench it into a molten salt bath at 280°C (below Ms point, Ms-29°C) for 120 minutes, during which the temperature fluctuation is controlled within ±3°C. After the insulation time is over, take it out immediately and cool it to room temperature in the air.

[0070] The isothermal quenching temperature and time above the Ms point can ensure the transformation of part of the bainite, which can divide the retained austenite into different units on the one hand and shorten the time for the bainite transformation to be completed on the other hand. The subsequent isothermal quenching temperature and time below the Ms point can ensure the transformation of the bainite and the simultaneous occurrence of bainite and martensite phase transformations. On the one hand, the martensite phase that is formed quickly and preferentially hinders the growth of bainite laths by occupying the supercooled austenite used for bainite phase transformation, and on the other hand, it provides a considerable number of nucleation points for the formation of bainite, thereby refining it. The bainite and martensite formed at the same time divide the blocky retained austenite retained in the first step again, ensuring the acquisition of multi-scale, multi-morphological and appropriate content retained austenite, as well as fine bainite lath structures.

[0071] A complex bainite steel with multi-scale, multi-morphological and appropriate content of retained austenite and fine-scale bainite lath structure was prepared; the scale of the blocky retained austenite is mostly concentrated between 0.4 and 5μm, followed by 5 and 8μm, and a small part of the scale is >8μm, the average volume fraction of retained austenite is 9.3%, and the average thickness of the bainite lath is about 140nm. According to the uniaxial tensile test, the tensile strength of the steel is 1454MPa, the yield strength is 1012MPa, and the elongation is 15.7%; according to the Charpy impact test, the impact absorption energy of the steel is 115J, the hardness is 456HV, and the comprehensive mechanical properties are excellent.

[0072] Example 4

[0073] A complex phase bainite steel and its preparation.

[0074] The chemical composition by mass percentage (wt.%) is: C 0.31%, Al 1.33%, Si 0.67%, Mn 1.87%, Cr 1.60%, Ni 0.35%, Mo 0.29%, W 0.23%, S 0.0055%, P 0.0043%, and the rest is Fe.

[0075] Prepare as follows:

[0076] a. The above raw materials are melted in a vacuum high-frequency induction furnace, and the molten steel is poured into a 50kg mold with a riser, and then slowly cooled to the ambient temperature (or room temperature) to obtain a steel ingot in a casting state, which is called an ingot; the ingot is turned to remove the outer surface oxide layer, the part containing inclusions at the bottom of the ingot is cut off, and the riser is removed, and then heated to about 1200°C, kept warm for 8 to 10 hours, and then taken out of the furnace for forging treatment, during which the final forging temperature is maintained at>860°C, and forged into a rod-shaped billet with a cross-sectional area of ​​40mm×60mm and a length of 800mm, air-cooled to room temperature, and finally cut with a cutting machine to obtain a smaller sample as a steel billet for subsequent processing, and coated with a high-temperature resistant and anti-oxidation coating.

[0077] b. Preparation of Dual-phase Bainite Steel

[0078] b-1. Based on the chemical composition of the steel, the Bs point of the steel was calculated by JMatPro software and determined by quenching dilatometer to be 490°C, the Ms point was 295°C, and the TTT curve determined that the bainite transformation completion time at 350°C was about 42 minutes.

[0079] b-2. Use a vacuum resistance furnace to heat the steel billet coated with high-temperature anti-oxidation coating to 1140-1180°C, keep it warm for 10-12 hours, and then slowly cool it for diffusion annealing, i.e., homogenization treatment, to eliminate composition and organizational heterogeneity.

[0080] b-3. Heat the homogenized steel billet to 930°C and keep it at that temperature for 30 minutes for austenitization.

[0081] b-4. Perform a two-step isothermal quenching treatment: immediately take out the austenitized sample and quench it into a 280℃ (below Ms point, Ms-15℃) salt bath for 10 minutes, then immediately quench it into a 350℃ (above Ms point, Ms+55℃) molten salt bath for further 60 minutes. During this period, control the temperature fluctuation within ±3℃. After the insulation time, take it out and air cool it to room temperature.

[0082] A complex bainite steel with multi-scale, multi-morphological and appropriate content of retained austenite and fine-scale bainite lath structure was prepared. The size of the blocky retained austenite is mostly concentrated between 0.4 and 4 μm, followed by 4 to 7 μm, and a small part of the size is > 7 μm. The average volume fraction of retained austenite is 8.3%, and the average thickness of the bainite lath is about 135 nm. According to the uniaxial tensile test, the tensile strength of the steel is 1436 MPa, the yield strength is 1030 MPa, and the elongation is 17.8%; according to the Charpy impact test, the impact absorption energy of the steel is 95 J and the hardness is 450 HV, showing excellent comprehensive mechanical properties.

[0083] Example 5

[0084] A complex phase bainite steel and its preparation, which is different from Example 1 in that the process parameters of the two-step isothermal quenching treatment in the preparation process are different, and the obtained complex phase bainite steel has differences in microstructure and mechanical properties. The specific preparation is as follows:

[0085] The chemical composition and preparation steps a to b-3 are the same as those in Example 1;

[0086] b-4. Perform a two-step isothermal quenching treatment: immediately take out the austenitized sample and quench it into a molten salt bath at 280°C (below Ms point, Ms-29°C) for 60 minutes, then immediately quench it into a molten salt bath at 350°C (above Ms point, Ms+41°C) for 60 minutes, during which the temperature fluctuation is controlled within ±3°C. After the insulation time, take it out immediately and cool it to room temperature in the air.

[0087] The holding time of 280°C below the Ms point is longer than that in Example 1. The purpose is to provide conditions for obtaining a large number of fine-scale bainite laths by means of the nucleation points provided by the quenched martensite and the relatively low isothermal temperature. At the same time, a longer bainite transformation is used to consume more austenite structure and diffuse more carbon inside it more fully into the surrounding austenite that has not undergone phase transformation, thereby increasing the stability of austenite and providing conditions for obtaining residual austenite of different scales. Further, a holding time of 350°C above the Ms point is used, which is the same as that in Example 1. That is, isothermal quenching at 350°C can avoid the generation of high-temperature temper brittleness. At this temperature, a holding time longer than that required for the theoretical transformation of bainite is used to ensure that the bainite transformation is completed. In this process, the remaining residual austenite will further undergo bainite transformation, so that the continuously formed bainite is further divided into structural units of different scales, providing a guarantee for the formation of multi-scale, multi-morphological and appropriate content residual austenite.

[0088] The process produces a microstructure with multi-scale and multi-morphological residual austenite distribution with appropriate content, fine bainite lath structure and tempered martensite. The specific organizational characteristics are: the size of the residual austenite is mostly concentrated between 0.4 and 3.5 μm, followed by 3.5 and 6 μm, and a small part of the size is greater than 6 μm; the average volume fraction of the residual austenite is 7.6%, and the average thickness of the bainite lath is about 122 nm. This microstructure makes the specific mechanical performance parameters of the steel in this embodiment: after uniaxial tensile test, the tensile strength is 1468 MPa, the yield strength is 1091 MPa, and the elongation is 15%; after Charpy impact test, the impact absorption energy is 108 J and the hardness is 468 HV. Compared with Example 1, although the tensile strength and hardness of the steel in this example have increased, its elongation, impact absorption energy and yield strength are lower than those in Example 1, especially its elongation is significantly lower than that in Example 1; the main reason may be that the more refined bainite laths containing high-density dislocations have promoted the increase in hardness, but the reduction in the size and content of the retained austenite has greatly reduced the TRIP effect produced by the retained austenite during the tensile deformation process, resulting in a decrease in elongation. At the same time, the holding time below the Ms point during the heat treatment of this example is significantly longer than that of Example 1, which increases energy consumption and increases cost investment on the one hand; on the other hand, it reduces production efficiency and limits industrial application.

[0089] Example 6

[0090] A complex phase bainite steel and its preparation, which is different from Example 1 in that the process parameters of the two-step isothermal quenching treatment in the preparation process are different, and the obtained complex phase bainite steel has differences in microstructure and mechanical properties. The specific preparation is as follows:

[0091] The chemical composition and preparation steps a to b-3 are the same as those in Example 1;

[0092] b-4. Perform a two-step isothermal quenching treatment: immediately take out the austenitized sample and quench it into a molten salt bath at 350℃ (Ms+41℃) above the Ms point for 10 minutes, then immediately quench it into a molten salt bath at 280℃ (Ms-29℃) below the Ms point for 120 minutes. During this period, the temperature fluctuation is controlled within ±3℃. After the insulation time, take it out immediately and cool it to room temperature in the air.

[0093] This embodiment adopts a heat treatment process of first above the Ms point and then below the Ms point. Its purpose is the same as that of Embodiment 3, but the specific operation is different. The holding time above the Ms point in this embodiment is shorter than that in Embodiment 3. The austenite is divided into larger structural units through partial transformation of bainite, and a higher content of supercooled austenite is retained; at the same time, the diffusion of carbon inside the bainite will make the surrounding untransformed austenite carbon-rich and retained to the next stage. In the subsequent isothermal quenching process below the Ms point, the supercooled austenite retained in the previous stage will further undergo bainite transformation while forming martensite. On the one hand, the austenite is divided into smaller structural units, and on the other hand, the austenite retained in the first stage is further carbon-rich through the diffusion of its internal carbon, which makes it possible to obtain multi-scale residual austenite and fine-scale bainite laths.

[0094] This embodiment has prepared a microstructure with multi-scale and multi-morphological residual austenite distribution of appropriate content, fine bainite lath structure and tempered martensite, and the specific organizational characteristics are: the size of the residual austenite is mostly concentrated between 0.4 and 5 μm, followed by 5 to 7 μm, and a small part of the size is greater than 7 μm; the average volume fraction of the residual austenite is 8.5%, and the average thickness of the bainite lath is about 135 nm. This microstructure makes the specific mechanical performance parameters of the steel in this embodiment: after uniaxial tensile test, the tensile strength is 1483MPa, the yield strength is 1010MPa, and the elongation is 14%; after Charpy impact test, the impact absorption energy is 110J and the hardness is 438HV. Compared with Example 1, the steel of this example has a higher tensile strength, and its yield strength and impact absorption work are similar, but its elongation is significantly lower, and its comprehensive mechanical properties are worse than those of Example 1; compared with Example 3, its tensile strength is higher, and its yield strength and absorption work are similar, but its elongation and hardness are significantly lower, and its comprehensive mechanical properties are also worse than those of Example 3.

[0095] Comparative Example

[0096] A complex phase bainite steel and its preparation, which has a similar chemical composition to the complex phase bainite steel of Example 1, but differs in that a single-step isothermal quenching treatment is used in the preparation process, as described below.

[0097] The chemical composition by mass percentage (wt.%) is specifically: C 0.30%, Al 1.20%, Si 0.70%, Mn 1.87%, Cr 1.65%, Ni 0.31%, Mo 0.46%, W 0.16%, S 0.0044%, P 0.0032%, and the rest is Fe.

[0098] Prepare as follows:

[0099] a. The operation is the same as step a of Example 1.

[0100] b. Preparation of Dual-phase Bainite Steel

[0101] b-1. Based on the chemical composition of the steel, the Bs point of the steel was calculated by JMatPro software and determined by quenching dilatometer to be 489°C, the Ms point was 296°C, and the TTT curve determined that the bainite transformation completion time at 350°C was about 52 minutes.

[0102] b-2. Heat the forged steel billet coated with high-temperature anti-oxidation coating to 1130-1170°C in a vacuum resistance furnace, keep it warm for 10-12 hours, and then slowly cool it for diffusion annealing, i.e., homogenization treatment, to eliminate composition and organizational heterogeneity.

[0103] b-3. Heat the homogenized steel billet to 930°C and keep it at that temperature for 30 minutes for austenitizing.

[0104] b-4. Perform single-step isothermal quenching treatment: immediately take out the austenitized sample and quench it into a mixed salt bath of sodium nitrite and potassium nitrate molten at 350°C above the Ms point for 120 minutes to complete the transformation of bainite. During this period, the temperature fluctuation is controlled within ±3°C. After the insulation time is over, take it out immediately and cool it to ambient temperature in the air.

[0105] The austempering temperature and time above the Ms point can ensure the transformation of part of the bainite. On the one hand, a bainite lath structure with fine size can be obtained, which divides the residual austenite into different units. On the other hand, the completion time of the bainite transformation is shortened.

[0106] The obtained product has the characteristics of multi-scale and multi-morphological distribution of retained austenite with appropriate content and fine bainite lath structure; the size of the blocky retained austenite is mostly concentrated in the range of 0.4-5μm, followed by 5-7μm, and a small part of the size is >7μm; the average volume fraction of retained austenite is 12.6%; and the average thickness of the bainite lath is about 143nm, see attached Figure 5Microstructure transmission electron microscope picture. According to the uniaxial tensile test, the tensile strength of the comparative steel is 1427MPa, the yield strength is 1188MPa, and the elongation is 16.8%. Figure 6 Engineering stress-strain curve; After Charpy impact test, the impact absorption energy of the comparative steel is 86J and the hardness is 434HV. The tensile strength, yield strength and hardness of the comparative steel are similar to those of Example 1, but its elongation and impact absorption energy are significantly lower than those of Example 1, and its comprehensive mechanical performance is significantly worse than that of Example 1.

[0107] In summary, the bainitic steel obtained by the present invention has a matrix structure composed of ultrafine structure bainitic laths, multi-scale and multi-morphological residual austenite, and a small amount of martensite. Compared with the single block or film-like residual austenite structure in most bainitic steels, and the residual austenite structure distributed in a narrow scale range, the residual austenite in the bainitic steel of the present invention is composed of large blocks, medium blocks, small blocks and films, showing multi-scale and multi-morphological characteristics, and having a wide scale distribution range and a relatively suitable volume fraction. This microstructure enables the steel of the present invention to show good plasticity and toughness while maintaining high strength and hardness, thereby having significantly excellent comprehensive mechanical properties. In addition, the preparation of the complex phase bainitic steel of the present invention has simple process, short process, easy operation, cost saving, and is conducive to large-scale industrial production and promotion and application.

Claims

1. A complex phase bainite steel containing a multi-scale and multi-morphological retained austenite structure, characterized in that: The chemical composition includes the following mass percentages: C 0.28-0.45, Al 0.6-1.35, Si0.65-1.1, Mn 1.6-2.0, Cr 1.5-1.8, Ni 0.28-0.5, Mo 0.28-0.5, W0.15-0.28, P<0.008, S<0.008, and the rest is Fe; The complex phase bainite steel is prepared by subjecting the steel billet to austenitization and then subjecting it to two-step isothermal quenching heat treatment, wherein the temperature of one step of the isothermal quenching heat treatment is set below the martensitic transformation start temperature of the steel billet, and the temperature of the other step of the isothermal quenching heat treatment is set above the martensitic transformation start temperature of the steel billet.

2. The multi-phase bainite steel containing a multi-scale and multi-morphological retained austenite structure according to claim 1, characterized in that: The starting temperature point of martensitic transformation, denoted as Ms point, is calculated from the isothermal transformation curve of the bainite transformation zone.

3. The complex phase bainite steel containing a multi-scale and multi-morphological retained austenite structure according to claim 2, characterized in that: The temperature of isothermal quenching heat treatment below the Ms point is between Ms-90℃ and Ms℃, and the temperature of isothermal quenching heat treatment above the Ms point is between Ms℃ and Ms+100℃.

4. The complex phase bainite steel containing a multi-scale and multi-morphological retained austenite structure according to claim 3, characterized in that: The temperature fluctuation of the two-step isothermal quenching heat treatment process was controlled within ±3°C.

5. The complex phase bainite steel containing multi-scale and multi-morphological retained austenite structure according to claim 2, characterized in that: The time for the two-step austempering heat treatment is as follows: The first step is to perform isothermal quenching below the Ms point for 0.5min to 65min, and the second step is to perform isothermal quenching above the Ms point for 30min to 120min; Or the first step is to perform isothermal quenching above Ms for 0.5min to 35min, and the second step is to perform isothermal quenching below Ms point for 30min to 130min.

6. The method for preparing a complex-phase bainite steel containing a multi-scale and multi-morphological retained austenite structure according to any one of claims 1 to 5, characterized in that: The method comprises the following preparation steps: a. Melting and casting into steel ingots according to the chemical composition, and then forging to obtain steel billets; b. Preparation of complex phase bainite steel: b-1. Use JMatPro software to calculate the isothermal transformation curve of the steel billet in the bainite transformation zone, determine the Ms point, and after confirming the Ms point using a quenching dilatometer, determine the process parameters suitable for the two-step isothermal quenching heat treatment of the steel billet; b-2. Homogenization treatment of steel billet; b-3, austenitizing the steel billet after homogenization treatment; b-4. Two-step isothermal quenching treatment: immediately quench the austenitized sample into a molten salt bath at Ms-50℃~Ms-10℃ and keep it warm for 3min~30min, then immediately quench the sample into a molten salt bath at Ms+10℃~Ms+60℃ and keep it warm for 30min~100min. After the warming time is over, take out the sample immediately and cool it to the ambient temperature in the air; Or immediately quench the sample after austenitization into a molten salt bath at Ms+20℃~Ms+60℃ and keep it warm for 5min~35min, then immediately quench the sample into a molten salt bath at Ms-50℃~Ms-10℃ and keep it warm for 30min~125min. After the holding time is over, take out the sample immediately and cool it to the ambient temperature in the air.

7. The method for preparing a complex-phase bainite steel containing a multi-scale and multi-morphological retained austenite structure according to claim 6, characterized in that: Step a, using a vacuum high-frequency induction furnace for melting, pouring molten steel into a mold, slowly cooling to the ambient temperature to obtain a steel ingot in a cast state; removing the oxide layer on the outer surface of the steel ingot, cutting off the bottom portion containing inclusions, and removing the riser, then heating to 1200° C., keeping the temperature for 8 to 10 hours, taking it out of the furnace for forging treatment, maintaining the final forging temperature greater than 860° C., forging it into a steel billet, and air cooling it to room temperature.

8. The method for preparing a complex-phase bainite steel containing a multi-scale and multi-morphological retained austenite structure according to claim 6, characterized in that: Step b-2: The homogenization treatment of the steel billet is as follows: The forged steel billet is heated to 1130-1180°C in a vacuum resistance furnace, kept warm for 10-12 hours, and then slowly cooled for diffusion annealing to eliminate composition and organizational heterogeneity.

9. The method for preparing a complex-phase bainite steel containing a multi-scale and multi-morphological retained austenite structure according to claim 6, characterized in that: Step b-3: The steel billet after homogenization is heated to 920-980° C. and kept at this temperature for 20-35 minutes to perform austenitization.

10. The method for preparing a complex-phase bainite steel containing a multi-scale and multi-morphological retained austenite structure according to claim 6, characterized in that: The salt bath used in step b-4 is a mixed salt bath of sodium nitrite and potassium nitrate.